Impact of tiered restrictions on human activities and the epidemiology of the second wave of COVID-19 in Italy - Manica, Mattia; Guzzetta, Giorgio; Riccardo, Flavia; Valenti, Antonio; Poletti, Piero; Marziano, Valentina; Trentini, Filippo; Andrianou, Xanthi; Mateo-Urdiales, Alberto; Del Manso, Martina; Fabiani, Massimo; Vescio, Maria Fenicia; et al. (My University, 2021)
To counter the second COVID-19 wave in autumn 2020, the Italian government introduced a system of physical distancing measures organized in progressively restrictive tiers (coded as yellow, orange, and red) imposed on a regional basis according to real-time epidemiological risk assessments. We leverage the data from the Italian COVID-19 integrated surveillance system and publicly available mobility data to evaluate the impact of the three-tiered regional restriction system on human activities, SARS-CoV-2 transmissibility and hospitalization burden in Italy. The individuals' attendance to locations outside the residential settings was progressively reduced with tiers, but less than during the national lockdown against the first COVID-19 wave in the spring. The reproduction number R(t) decreased below the epidemic threshold in 85 out of 107 provinces after the introduction of the tier system, reaching average values of about 0.95-1.02 in the yellow tier, 0.80-0.93 in the orange tier and 0.74-0.83 in the red tier. We estimate that the reduced transmissibility resulted in averting about 36% of the hospitalizations between November 6 and November 25, 2020. These results are instrumental to inform public health efforts aimed at preventing future resurgence of cases.
Keywords: Italy; Citrus sinensis; SARS coronavirus; ARIMA; Mathematical Modeling; COVID-19